Decarbonizing Aviation: A Comparative Analysis of Power-to-Liquid and Biomass-Derived Sustainable Fuels - Ren Sijie (MATEC Web of Conferences)
The aviation industry is one of the highest emitters of greenhouse gases globally, and thus, the call to become carbon neutral is an urgent one. Two possible paths of production of sustainable aviation fuel (SAF) are considered here: the Power-to-Liquid (PtL) pathway and biomass conversion. The PtL pathway makes use of renewable electricity to decompose water and form hydrogen through electrolysis, utilizing captured carbon dioxide to form liquid hydrocarbons through Fischer-Tropsch synthesis. While promising, PtL suffers from problems of energy inefficiency, production inefficiencies, and financial constraints. Biomass conversion, however, involves the use of organic feedstocks, gasification and fermentation of the feedstocks to produce liquid fuels. While biomass- based fuels have the advantage of compatibility with current infrastructure, they have land-use problems, feedstock renewability, and lifecycle emissions concerns. By contrasting these routes in terms of energy efficiency, economic viability, and environmental friendliness, this research underlines the necessity of policy action and technological breakthroughs to optimize SAF production. The findings indicate that PtL and biofuels will have supporting roles to play in energizing a decarbonized aviation industry, where persistent innovation is vital to the evolution of sustainable, affordable, and scalable solutions.